2012
DOI: 10.1007/s00425-012-1800-1
|View full text |Cite
|
Sign up to set email alerts
|

Tonoplast of Beta vulgaris L. contains detergent-resistant membrane microdomains

Abstract: The experiments conducted on tonoplast of Beta vulgaris L. roots were performed to identify detergent-resistant lipid-protein microdomains (DRMs, interpreted as lipid rafts).The presence of DRMs can be found when dynamic clustering of sphingolipids, sterols, saturated fatty acids is registered, and the insolubility of these microdomains in nonionic detergents at low temperatures is proven. The elucidation of tonoplast microdomains has been based on results obtained with the aid of high-speed centrifuging in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…Recently, similar sphingolipid desaturases have been characterized in the diatom T. pseudonana (Michaelson et al, 2013;Tonon et al, 2005). In yeast, and in Arabidopsis, regions within the vacuolar bilayer, enriched in sphingolipids and sterols (Chung et al, 2003;Finnigan et al, 2011), have been identified as essential to the function of vacuolar-ATPases (Ozolina et al, 2013;Yoshida et al, 2013). Vacuolar-ATPases are the proton pumps in plants (reviewed in Martinoia et al, 2007) that provide energy for NO 3 2 transport into the vacuole via NO 3 2 ClC transporters identified in this study.…”
Section: Nitrate Uptake Into the Vacuole A Competitive Advantage In mentioning
confidence: 64%
See 1 more Smart Citation
“…Recently, similar sphingolipid desaturases have been characterized in the diatom T. pseudonana (Michaelson et al, 2013;Tonon et al, 2005). In yeast, and in Arabidopsis, regions within the vacuolar bilayer, enriched in sphingolipids and sterols (Chung et al, 2003;Finnigan et al, 2011), have been identified as essential to the function of vacuolar-ATPases (Ozolina et al, 2013;Yoshida et al, 2013). Vacuolar-ATPases are the proton pumps in plants (reviewed in Martinoia et al, 2007) that provide energy for NO 3 2 transport into the vacuole via NO 3 2 ClC transporters identified in this study.…”
Section: Nitrate Uptake Into the Vacuole A Competitive Advantage In mentioning
confidence: 64%
“…Vacuolar membrane lipids are poorly characterized in diatoms, but those that make up the vacuolar membranes in plants that store NO 3 2 provide a starting point for consideration of the composition of P. tricornutum vacuolar membranes. In vascular plants, the majority of vacuolar membrane lipids are phospholipids PE and PC, sterols, and sphingolipids, with sterols and sphingolipids comprising 30% and 10 to 20%, respectively (Ozolina et al, 2013;Yoshida and Uemura, 1986;reviewed in Zhang et al, 2015). Within the lipid cluster subset, we highlighted five genes encoding proteins with functions that are putatively well suited to vacuolar membrane lipid biosynthesis in P. tricornutum.…”
Section: Nitrate Uptake Into the Vacuole A Competitive Advantage In mentioning
confidence: 99%
“…Alternatively, the presence of VHA-a2 and VHA-a3 in DRMs could simply be due to residual tonoplast membranes in the PMenriched samples. Indeed, the presence of DRMs in tonoplast preparations has recently been confirmed (Ozolina et al, 2012) and is in agreement with the fact that both sterols and sphingolipids, two classes of lipids typically enriched in DRMs, are present in amounts comparable to the PM (Yoshida and Uemura, 1986). Here, using the sterol binding probe filipin III, we have not only shown that sterols are indeed present in the tonoplast of Arabidopsis root tip cells but also that they still reach the tonoplast when ER export is blocked by BFA treatment in the sensitized GNL1-BFA S background.…”
Section: Direct Delivery From the Er To The Tonoplastmentioning
confidence: 96%
“…The stimulus for our investigation was absence of plausible knowledge about the structure and the functions of lipid-protein microformations in cell organelles, as well as the interest to the unusual membrane microinclusions registered in our observations earlier [3]. In particular, the domain structure of vacuolar membranes has not been plausibly scanned and investigated before.…”
Section: Introduction and Problem Statementmentioning
confidence: 99%
“…As obvious from earlier publications of several authors, the cell membrane is characterized by mobile lateral nonhomogenieties of its lipid content represented in the form of microinclusions [1] [2] [3]. These microinclusions may be studied in experiments presuming 1) visualization of the cell membranes with finding out examples of such microinclusions and 2) investigation of their characteristics.…”
Section: Introduction and Problem Statementmentioning
confidence: 99%